1991
DOI: 10.1097/00006123-199106000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Occipital meningoceles in patients with the Dandy-Walker syndrome

Abstract: Occipital cephaloceles in the Dandy-Walker syndrome are not rare. To date, 28 cases have been reported. We report on 8 cases of associated occipital meningocele, totalling 16% of all patients with the Dandy-Walker syndrome in our series. In all patients, communication existed between the posterior fossa cyst and the occipital meningocele. In 2 patients, the occipital meningocele disappeared after cerebrospinal fluid shunting and never required surgical repair. It appears that the cranial defect had ossified an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…According to Bindal et al[ 20], 28 cases of occipital cephalocele associated with the Dandy-Walker syndrome included meningocele, encephalocele, or encephalocystomeningocele and 11 of the 28 cases had pure occipital meningocele. Overall 16% of cases of Dandy-Walker syndrome were associated with occipital meningocele in this series.…”
Section: Discussionmentioning
confidence: 99%
“…According to Bindal et al[ 20], 28 cases of occipital cephalocele associated with the Dandy-Walker syndrome included meningocele, encephalocele, or encephalocystomeningocele and 11 of the 28 cases had pure occipital meningocele. Overall 16% of cases of Dandy-Walker syndrome were associated with occipital meningocele in this series.…”
Section: Discussionmentioning
confidence: 99%
“…Shunting of both the lateral ventricle and the posterior fossa cyst is the current treatment in children with DWM and associated aqueductal stenosis [5, 21, 22]. In 92%, control of hydrocephalus, reduction of the intracranial pressure and of the size of the posterior fossa cyst could be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…(1) The complication rate of simultaneous shunting seems to be higher: Gerszten and Albright [6] observed twice as many complications in ventriculoperitoneal plus cystoperitoneal shunts than in monocompartmental shunts, with the shunt malfunction more likely to be caused by the cystoperitoneal component [5]. (2) High failure rates of ETV in children have been reported by some authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that if only a meningocele is present in the setting of Dandy-Walker syndrome, it can resolve after shunt placement without surgery, with subsequent ossification [8]. However, in this case the protruding intracranial contents were removed at least 1 year earlier in a surgical procedure for which the description was not available and there was no evidence of bone formation within the residual occipital bone defect.…”
Section: Discussionmentioning
confidence: 89%